Cerebral Autosomal-Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy – CADASIL - Brondani, Rosane; Almeida, Andrea Garcia; de Araújo, Vicenzo Zarpellon; Bianchin, Larissa; Mota, Suelen Mandelli; Krammer, Bárbara Reis; Marafon, Martina Camerini; Mazzocato, Eduardo de Carvalho; Bianchin, Marino Muxfeldt (Clinical and Biomedical Research, 2017)
We report here neuroimaging findings of a 41 years-old female with molecular diagnosis of CADASIL (Cerebral Autosomal-Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy). CADASIL, the most common form of hereditary stroke, is characterized by headaches and relapsing strokes. More than 95% of patients present mutations of NOTCH3 gene. MRI, the best neuroimaging modality to investigate CADASIL can show lacunar infarcts and less-well demarcated T2 weighted hyperintensities characteristically located in subcortical white matter. There is no specific treatment for CADASIL. Anti-platelet agents such as aspirin might help to prevent new strokes. Other symptoms, like headache, seizures, or other neuropsychiatric manifestations should be appropriately treated.